2020
DOI: 10.1155/2020/9716581
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of Glucose Oxidase by Aspergillus tubingensis CTM 507 Randomly Obtained Mutants and Study of Its Insecticidal Activity against Ephestia kuehniella

Abstract: In order to enhance the production of glucose oxidase (GOD), random mutagenesis of Aspergillus tubingensis CTM 507 was performed using the chemical and physical mutagens: nitric acid and UV irradiation, respectively. The majority of the isolated mutants showed good GOD production, but only some mutants presented a significant overproduction, as compared with the parent strain. The selected mutants (19 strains), showing an overproduction larger than 200%, are quite stable after three successive subcultures. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A study [ 62 ] revealed that N-methyl-N-nitro-N-nitrosoguanidine (MNNG) and ethidium bromide caused the wild Aspergillus niger to change, and the enzyme activity of the mutants increased by 282% and 202%, respectively. It was believed that the random mutagenesis of Aspergillus tubingensis using nitric acid and UV irradiation can screen for some mutants, leading to a significant yield improvement [ 66 ]. Meanwhile, Khattab et al [ 63 ] selected mutants of Aspergillus niger and used them for protoplast fusion in intraspecific hybridization, resulting in fusants with higher activity than the original strain (from 114.5 to 332.1%).…”
Section: Strategies For Improving Glucose Oxidase Yieldsmentioning
confidence: 99%
“…A study [ 62 ] revealed that N-methyl-N-nitro-N-nitrosoguanidine (MNNG) and ethidium bromide caused the wild Aspergillus niger to change, and the enzyme activity of the mutants increased by 282% and 202%, respectively. It was believed that the random mutagenesis of Aspergillus tubingensis using nitric acid and UV irradiation can screen for some mutants, leading to a significant yield improvement [ 66 ]. Meanwhile, Khattab et al [ 63 ] selected mutants of Aspergillus niger and used them for protoplast fusion in intraspecific hybridization, resulting in fusants with higher activity than the original strain (from 114.5 to 332.1%).…”
Section: Strategies For Improving Glucose Oxidase Yieldsmentioning
confidence: 99%
“…Therefore, they indicated that new-produced rGOX is ideal for developing bio-electrochemical instrumentations . 11,19,95 In another study, Kriaa et al 96 reported an improvement in the GOX secretion from A. tubingensis achieved by random mutagenesis. Recombinant production of GOX using various yeasts leads to the generation of hyperglycosylated variants with reduced activity.…”
Section: Bacterial Hosts For the Gox Genementioning
confidence: 99%
“…Therefore, they indicated that new‐produced rGOX is ideal for developing bio‐electrochemical instrumentations 11,19,95 . In another study, Kriaa et al 96 . reported an improvement in the GOX secretion from A. tubingensis achieved by random mutagenesis.…”
Section: Bacterial Hosts For the Gox Genementioning
confidence: 99%